Penguindrum. Vol. 2 - Ikunichawder; Ikuhara, Kunihiko, 1964- (Seven Seas Entertainment, 2019)
"A DESPERATE SEARCH. The hunt for the Penguindrum is on! Kanba and Shoma are doing everything they can to track it down- but how can they find something when they don't even know what it is?"--Page [4] of cover.